COMPARISON OF PANGKAH KULON VILLAGE, GRESIK REGENCY WITH INTAN JAYA VILLAGE, KAMPAR REGENCY IN PUBLIC SERVICE IN 2017 - Yuza, Ahmad Fitra; Deliarnoor, Nandang Alamsah; Nazsir, Nasrullah; Teguh, Priyo (Advances in Social Sciences Research Journal, 2018)
This study discusses the comparison of two village administrations in implementing public service, especially village level demography services. Service at village level is very urgent consider the village is a semi-autonomous government. The position of village government in the service of population administration based on the principle of assistance, is set forth in Law Number 24 Year 2013 regarding the amendment to Law Number 23 of 2006 concerning the administration of population in Article 7 Paragraph (1) Point f reads that the assignment to the village to organize some of the administrative affairs of population based on the principle of co-administration. Pangkah Kulon, a village located in Gresik Regency has the best service innovation to the local community, meanwhile the Village Intan Jaya, in Kampar regency, was far from service standards. Methods and research approaches were conducted using qualitative research method with a descriptive approach, data collection through observation method, in-depth interview, documentation and focus group discussion. Informant determination technique was done by criterion-based selection technique. The results of the research indicate that the service of Intan Jaya Village cannot be well organized which is seen from not fulfilling the standard of service, the service procedure which is difficult to be understood by the society, the recruitment of old system employees, the absence of service innovation, the absence of system in response to various complaints of society, service layout.